2019
DOI: 10.1038/s41598-019-55296-3
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic suppression dramatically changes the intracellular metabolic profile of multiple cancer cell lines in a mitochondrial metabolism-dependent manner

Abstract: Most cancer cells rely on glycolysis to generate ATP, even when oxygen is available. However, merely inhibiting the glycolysis is insufficient for the eradication of cancer cells. One main reason for this is that cancer cells have the potential to adapt their metabolism to their environmental conditions. In this study, we investigated how cancer cells modify their intracellular metabolism when glycolysis is suppressed, using PANC-1 pancreatic cancer cells and two other solid tumor cell lines, A549 and HeLa. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 60 publications
7
138
0
Order By: Relevance
“…Importantly, tumors are not metabolically homogeneous and the glycolytic or oxidative phenotype can depend on nutrient availability and the microenvironment. For instance, Shiratori et al [23] demonstrated that the suppression of glycolysis in different cancer cells including pancreatic (Panc-1 cell line), induces a dramatic switch towards the OXPHOS profile. This switch is characterized by an increase in enzymes involved in TCA cycle and OXPHOS, as well as an increase in mitochondrial dynamics and mitochondrial membrane potential.…”
Section: Glycolytic Oxphos or Hybrid Phenotype?mentioning
confidence: 99%
“…Importantly, tumors are not metabolically homogeneous and the glycolytic or oxidative phenotype can depend on nutrient availability and the microenvironment. For instance, Shiratori et al [23] demonstrated that the suppression of glycolysis in different cancer cells including pancreatic (Panc-1 cell line), induces a dramatic switch towards the OXPHOS profile. This switch is characterized by an increase in enzymes involved in TCA cycle and OXPHOS, as well as an increase in mitochondrial dynamics and mitochondrial membrane potential.…”
Section: Glycolytic Oxphos or Hybrid Phenotype?mentioning
confidence: 99%
“…It has been suggested that common hexoses other than glucose, such as galactose and fructose, are also involved in the growth and metastasis of cancer cells. Galactose has been shown to induce OXPHOS-dependent metabolism and suppress the growth and metastasis of cancer cells [ 84 , 85 , 86 ]. On the other hand, fructose has been shown to promote liver metastasis in colon cancer and breast cancer [ 87 ].…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…Human platelets, a fresh source of viable mitochondria, have been described to rely on oxidative phosphorylation and reflect mitochondrial function of other, more metabolically active tissues [35][36][37][38]. Also cancer cells, long believed to rely solely on glycolysis, have now been described to upregulate their mitochondrial metabolism under certain conditions and rely on mitochondrial function for several cancerogenic processes [39,40]. Even though there are important differences between primary hepatocytes, HepG2 cells and human platelets, our data indicate that they show a relative comparable sensitivity towards drug-induced mitochondrial dysfunction, as indicated by the similar IC 50 values determined in this study.…”
Section: Plos Onementioning
confidence: 99%